Social partnership in conditions of the resource center - Utemuratova, B.K. (Вестник Карагандинского университета, 2016)
The article examines the effectiveness of social partnership with the universities in conditions of profile training resource center. The features and advantages of the Resource Center have been allocated. Analyzed the content and structure of the course subjects on the basis of university technology, such as «Fundamentals of Accounting», «Fundamentals of Entrepreneurship», «Fundamentals of Driving», which provide preprofessional training of students in technical specialties that are in demand today and in the world market. The author shows the educational opportunities of the network of schools to provide students with choices like training courses, as well as ways of organizing learning activities with regard to their educational needs.
Keywords: Social Partnership; informatization; self-determination; pre-professional; Resource Center for Profile Training (RCPT); new technologies; cooperation